Speaking Anxiety in English Conversation Classrooms Among Thai Students - Songyut Akkakoson (UUM Press, 2016)
Purpose â€" This paper reports on a part of a larger research project concerning the conceptualisation of English language speaking-in-class anxiety, attitudes to speaking English in class and self-ratings of English-speaking ability, and perceived sources of this situation-specific anxiety.   Methodology â€" The participants in this study were 282 Thai university students of English as a foreign language (EFL) studying English Conversation courses at a university in Thailand. Levels of anxiety (on average and by dimensions) were investigated through questionnaires adapted from the Foreign Language Classroom Anxiety Scale (FLCAS). Attitudes towards oral English, self-ratings of English-speaking ability and sources of speaking anxiety were collated through semi-structured interview forms.   Findings â€" The quantitative analysis indicated the existence of speaking-in-class anxiety among Thai EFL students at a moderate level. Levels of anxiety by dimensions, namely test-anxiety (TA), fear of negative evaluation (FNE) and communication apprehension (CA), were found to be moderate as well. However, TA and FNE were significantly dominant performance anxieties. Qualitatively, studentsâ€™ positive attitudes towards speaking English in the classroom were reflected, whereas a negative rating for their spoken English ability was reported. Finally, the limited repertoire of studentsâ€™ vocabulary was found to be their major source of speaking anxiety.   Significance â€" This research urges awareness of anxiety-provoking factors in the EFL classroom as learnersâ€™ ability to communicate satisfactorily is both the learnersâ€™ goal of learning and the instructorâ€™s goal of teaching. The findings have pedagogic implications in terms of affective aspects of learning, for students when making an effort to overcome speaking-in-class anxiety and for instructors when attempting to create a low-anxiety classroom.